Molecular immune response of channel catfish immunized with live theronts of Ichthyophthirius multifiliis. (July 2016) - Xu, De-Hai; Zhang, Qi-Zhong; Shoemaker, Craig A.; Zhang, Dunhua; Moreira, Gabriel S.A.
Abstract: The parasite Ichthyophthirius multifiliis (Ich) has been reported in various freshwater fishes worldwide and results in severe losses to both food and aquarium fish production. The fish surviving natural infections or immunized with live theronts develop strong specific and non-specific immune responses. Little is known about how these immune genes are induced or how they interact and lead to specific immunity against Ichthyophthirius multifiliis in channel catfish Ictalurus punctatus . This study evaluated the differential expression of immune-related genes, including immunoglobulin, immune cell receptor, cytokine, complement factor and toll-like receptors in head kidney from channel catfish at different time points after immunization with live theronts of I. multifiliis . The immunized fish showed significantly higher anti-Ich antibody expressed as immobilization titer and ELISA titer than those of control fish. The vast majority of immunized fish (95%) survived theront challenge. Expression of IgM and IgD heavy chain genes exhibited a rapid increase from 4 hour (h4) to 2 days (d2) post immunization. Expression of immune cell receptor genes (CD4, CD8-α, MHC I, MHC II β, TcR-α, and TcR-β) showed up-regulation from h4 to d6 post immunization, indicating that different immune cells were actively involved in cellular immune response. Cytokine gene expression (IL-1βa, IL-1βb, IFN-γ and TNF-α) increased rapidly at h4 post immunization and were at an up-regulated level until d2 compared to the bovine serum albumin control. Expression of complement factor and toll-like receptor genes exhibited a rapid increase from h4 to d2 post immunization. Results of this study demonstrated differential expression of genes involved in the specific or non-specific immune response post immunization and that the vaccination against Ich resulted in protection against infection by I. multifiliis . Highlights: Evaluated expression of immune genes in catfish after immunized with live Ich theront. Immunized fish showed higher survival and anti-Ich antibody than control fish. Expression of IgM and IgD genes increased rapidly from h4 to d2 post immunization. Cell receptor genes are actively involved in cellular immune response. Immune genes are involved in specific or non-specific immune response.